Effect of carbon content on the structure and electronic properties of silicon oxycarbide anodes for lithium-ion batteries: a first-principles study. Issue 9 (7th March 2015) - Liao, Ningbo; Zheng, Beirong; Zhou, Hongming; Xue, Wei
<x xml:space="preserve">Abstract</x> Silicon oxycarbide (SiCO) shows a three times larger lithium capacity than does graphite. This work provides an insight into the lithiation mechanism of SiCO as anode material for Li-ion batteries.